The role of the regulatory framework for innovation activities: The EU ETS and the German paper industry - Karoline S. Rogge; Joachim Schleich; Philipp Haussmann; Annette Roser; Felix Reitze (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2011)
Based on a research framework which combines environmental economics and innovation studies, we explore the relevance of the regulatory framework for innovation activities in the German paper industry, with a focus on climate poli-cies. Innovation activities considered include research and development, adop-tion and organizational change. Empirically, we mainly rely on the survey data of paper producers and technology providers. Findings suggest that innovation activities are mainly governed by market factors and (as yet) are hardly affected by the European Emission Trading System and other climate policies. Also, the impact of these policies on innovation activities is lower for technology providers than for paper producers. However, the majority of companies expect the ef-fects of the regulatory climate policy framework on innovation to increase by 2020.
urn:nbn:de:0011-n-1539549
Keywords: 330